Coordinating Climate and Trade Policies : Pareto Efficiency and the Role of Border Tax Adjustments - Keen, Michael (IMF Working Papers; Working Paper, 2012)
This paper explores the role of trade instruments in globally efficient climate policies, focusing on the central issue of whether some form of border tax adjustment (BTA) is warranted when carbon prices differ internationally. It shows that tariff policy has a role in easing cross-country distributional concerns that can make non-uniform carbon pricing efficient and, more particularly, that Pareto-efficiency requires a form of BTA when carbon taxes in some countries are constrained, a special case being identified in which this has the simple structure envisaged in practical policy discusions. It also stresses-a point that has been overlooked in the policy debate-that the efficiency case for BTA depends critically on whether climate policies are pursued by carbon taxation or by cap-and-trade.